2016
DOI: 10.1111/jre.12395
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial cell response to health and disease associated oral biofilm models

Abstract: Background and ObjectiveDifferent bacteria differentially stimulate epithelial cells. Biofilm composition and viability are likely to influence the epithelial response. In vitro model systems are commonly used to investigate periodontitis‐associated bacteria and their interactions with the host; therefore, understanding factors that influence biofilm–cell interactions is essential. The present study aimed to develop in vitro monospecies and multispecies biofilms and investigate the epithelial response to these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 22 publications
5
43
0
Order By: Relevance
“…CXCL1 (Groα) together with IL‐8 are major chemotaxins for neutrophils. This chemokine is upregulated in gingival epithelial cells, and Ramage et al have shown that CXCL1 and CSF2 levels were significantly increased in oral epithelial cell cultures treated with biofilms, particularly associated with a mixed species biofilm containing F. nucleatum and P. gingivalis , as was seen in this study. Regarding a role in periodontitis, both CXCL1 and CXCL2 are expressed in the junctional epithelium potentially contributing to attempts to maintain homeostasis .…”
Section: Discussionsupporting
confidence: 77%
“…CXCL1 (Groα) together with IL‐8 are major chemotaxins for neutrophils. This chemokine is upregulated in gingival epithelial cells, and Ramage et al have shown that CXCL1 and CSF2 levels were significantly increased in oral epithelial cell cultures treated with biofilms, particularly associated with a mixed species biofilm containing F. nucleatum and P. gingivalis , as was seen in this study. Regarding a role in periodontitis, both CXCL1 and CXCL2 are expressed in the junctional epithelium potentially contributing to attempts to maintain homeostasis .…”
Section: Discussionsupporting
confidence: 77%
“…Polymicrobial communities are able to form biofilms upon this vast variety of substrates [5••, 6, 7]. It is now generally well understood that dental plaque biofilms contain many resident species that modulate one another, their environment, and also the host response [8][9][10]. Despite the widely acknowledged presence of yeasts within the oral cavity, their active role and participation in oral diseases is generally perceived to be restricted to mucosal-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There is still insufficient data to distinguish the relative roles of oral bacterial lipopolysaccharide (LPS) and surface-associated and secreted proteins in cytokine induction. Various recognized periodontal pathobionts trigger distinct types of inflammatory responses (87)(88)(89), and some (e.g., Porphyromonas gingivalis) can modulate that by interfering with chemokine production (90).…”
mentioning
confidence: 99%
“…We used a human immortalized oral keratinocyte cell line (OKF6/TERT-2), which has been previously used as a model to study the interaction of oral bacteria with human epithelial cells (88,91). Cells and filtered medium from the same D. oralis cultures used for proteomic analyses were applied to epithelial cells in culture, and the production of 13 human inflammatory cytokines/chemokines was measured after 48 h using bead-based immunoassays.…”
mentioning
confidence: 99%